Online Business Socialization During the MSME Pandemic Awakens Case Study of Inner Village Youth Suka Maju Deli Serdang - Zuriani Ritonga; Hayanuddin Safri; Bayu Eko Broto; Sutoyo; Chairul Baria (PT Inovasi Pratama Internasional, 2022)
Online business is one way of growing and revitalizing the economy during the COVID-19 pandemic, village youth will be the perpetrators of the online business. The interests and talents and willingness of teenagers to like to advance towards the online business are very lively, with a strong, unidirectional and significant correlation. The participants' understanding of the explanation and explanation of the PkM team on how to use the internet as an online medium that can be used as a business field to increase income. In this socialization, there were also several obstacles for the young people of the inner village, in carrying out or working on this online business, including the lack of a deep understanding of the platforms that will be used in the online business as well as the lack of infrastructure such as computers, laptops and smartphones and even capital.